Genomic imprinting in mouse blastocysts is predominantly associated with H3K27me3 - Laura Santini (Nature Portfolio, 2021)
In most mammals, imprinted genes contain epigenetic marks that differ in each parental genome and control their parent-of-origin-specific expression. Here, the authors map imprinted genes in mouse preimplantation embryos and find that imprinted gene expression in blastocysts is mainly dependent on Polycomb-mediated H3K27me3-associated gene silencing.